Making silver jewellery - Muttitt, Louise Mary (Crowood Press, 2014)
Silver is an exciting and versatile material for jewellery makers, both beginners and the more advanced, and nothing beats the satisfaction of creating and making your own designs. This book shows you how. Full of inspiring ideas and finished pieces, it explains over forty processes including the more advanced techniques such as fold forming and keum-boo and encourages the reader to experiment with their own designs. Contents include: Step-by-step explanations with bench tips from the author's own experience; advice on the jewellery process, including how to gather inspiration for designs and considerations for making wearable jewellery; a chapter dedicated to the surface finishing and polishing of silver to give your designs a professional finish. This is an accessible introduction to making silver jewellery with progression to more advanced techniques. Beautifully illustrated with 324 colour photographs.--Provided by publisher.